2018
DOI: 10.14336/ad.2017.1001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging and Glucagon-like Peptide 2 on Intestinal Microbiota in SD Rats

Abstract: Recent research suggests that intestinal microbiota affect the aging process. Glucagon-like peptide 2 (GLP-2), a growth factor found in the intestinal mucosal epithelium, reduces intestinal permeability and affects intestinal microbiota. The relationship between aging, GLP-2, and intestinal microbiota are still not well understood. The current study examined the influence of aging and GLP-2 on the intestinal microbiota of rats. Twelve 3-month old male SD rats were randomly divided into two groups: a young cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Knowledge in this area is still sparse as structural modulation of the gut microbiome has only been reported at a relative low level of resolution (phylum/genus level) following treatment with agonists selective for the GLP-1 3134 and GLP-2 25,35 receptors. In addition, most current approaches for analyzing gut microbiome data rely on comparisons to reference genomes 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge in this area is still sparse as structural modulation of the gut microbiome has only been reported at a relative low level of resolution (phylum/genus level) following treatment with agonists selective for the GLP-1 3134 and GLP-2 25,35 receptors. In addition, most current approaches for analyzing gut microbiome data rely on comparisons to reference genomes 36 .…”
Section: Introductionmentioning
confidence: 99%
“…However, whether GLP-2 could ameliorate the intestinal microbiota dysbiosis of SBS has not been studied. Yu Hu and colleagues [ 13 ] demonstrated that GLP-2 treatment resulted in the increase of several probiotics and the decrease of some pathogenic bacterial genera in intestine of aged rats. Therefore, we performed this study to investigate the colonic microbiota of SBS rats with or without GLP-2 intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study had found that several days of antibiotics may lead to a reduction of potentially anti-inflammatory Clostridia and an increase of pro-inflammatory Proteobacteria [ 4 ]. According to previous studies, GLP-2 may alleviate intestinal microbiota dysbiosis [ 13 ]. As we expected, GLP-2 treatment significantly downregulated the relative abundance of pro-inflammatory Proteus genus in SBS rats, and increased the relative abundance of potentially anti-inflammatory inhibitory Clostridium genus from Clostridia class in SBS rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from GLP-1 secretion, L cells sense pathogen-derived molecules, likely suggesting that GLP-1 functions as an AMP (Greiner and Bäckhed, 2016; Lebrun et al, 2017). Aging has been associated with decreased number of L cells, accounting for the loss of GI tract immunological tolerance (Drozdowski and Thomson, 2006; Wu et al, 2018). Aside from L cells, GALT dysfunction may be linked to the loss of membranous (M) cells, known for producing secretory immunoglobulin A (SIgA), an IEC immune protector (Mantis et al, 2011; Kobayashi et al, 2013; Sato S. et al, 2014; Ohno, 2016).…”
Section: Beta Amyloid: Friend or Foe?mentioning
confidence: 99%